PERAN ORANG TUA ASUH BAGI PEMENUHAN KEBUTUHAN HIDUP ANAK DI PANTI ASUHAN PERMATA BALI MENURUT TEORI MASLOW DITINJAU DARI LUKAS 15:11-32 - Hery Susanto; Daud Lumba’a (SAGACITY : Journal of Theology and Christian Education, 2021)
Foster parents play an important role in the development of children and the fulfillment of their needs. Maslow's theory emphasizes the human right to obtain the fulfillment of the necessities of life. Luke 15:11-32 describes the relationship between father and son when there is disharmony in the family. Therefore, in this article, we will describe the role of foster parents for children in orphanages in terms of Luke 15:11-32.